An acetylisosorbide ester bio-based plasticizer and a preparation method and application thereof
Patent Information
- Application Number
- CN202410154473.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-04
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-02-04
AI Technical Summary
Existing bio-based plasticizers have problems in improving the performance of polyvinyl chloride (PVC) materials, such as poor plasticizing effect, insufficient thermal stability, high migration, and the need to use multiple plasticizers in combination.
Acetyl isosorbide oleate bio-based plasticizers were prepared by reacting epoxy isosorbide oleate with acetic anhydride and a strongly acidic cation exchange resin, introducing four acetyl side groups to form plasticizers with stronger interaction forces.
It achieves excellent plasticizing effect on PVC, improves elongation at break and thermal stability, reduces migration and mass loss rate, and meets the requirements of green chemistry.
Smart Images

Figure BDA0004696657210000091 
Figure BDA0004696657210000101 
Figure HDA0004696657220000011
Abstract
Description
Technical Field
[0001] This invention belongs to the field of plasticizer technology application, specifically relating to an acetylsorbitol ester bio-based plasticizer and its preparation method and application. Background Technology
[0002] Polyvinyl chloride (PVC) is a common thermoplastic material and the second most popular plastic after polyethylene. PVC has excellent mechanical properties, good chemical corrosion resistance and low cost, so it is widely used in many everyday material fields such as electronic device packaging, medical devices, transportation equipment, children's toys and food packaging. However, pure PVC products exhibit strong rigidity and brittleness, and it is necessary to add additives to reduce the processing difficulty and improve the performance of PVC products. The plastic additive with the largest amount of plastic is plasticizer. Although the current plasticizing theory cannot be fully applied to all plasticizers, three classic plasticizing theories are widely accepted: (1) Lubrication theory: Plasticizer diffuses between polymer macromolecular chains, separates and lubricates macromolecular chains, reduces friction and thus plays a plasticizing role; (2) Gel theory: Plasticizer molecules combine with macromolecular chains under the action of weak forces, destroy the connection between macromolecular chains, and thus achieve the plasticizing effect; (3) Free volume theory: Plasticizer increases the free volume of polymer, so plasticizer should have a relatively low molecular weight but a relatively large molecular size. Currently, over 500 types of plasticizers have been industrialized. In 2020, my country's total plasticizer production reached over 7 million tons, ranking first in the world, with phthalate plasticizers accounting for as much as 74%. Although phthalate plasticizers are low in cost and have good plasticizing effects, they have high migration rates, are toxic to animals and humans, and cause some environmental pollution. According to European regulations 2000 / 60 / EC and 1907 / 2006 / EC, some phthalates have been banned. Therefore, finding a non-toxic, renewable, bio-based raw material to synthesize efficient and environmentally friendly plasticizers is one of the current research directions.
[0003] Commonly used bio-based plasticizers include vegetable oils, lactic acid, glycerides, succinates, isosorbide esters, and citrates. Isosorbide, a heterocyclic diol obtained through modification via starch and cellulose hydrolysis, possesses excellent thermal stability and biodegradability. Compared to the benzene ring in phthalates, the heterocyclic diol in isosorbide provides a degree of rigidity while avoiding the toxic effects of benzene on the human body. Isosorbide esters synthesized from isosorbide have two branches, similar in structure to phthalates. Some studies have reported that different isosorbide esters can be synthesized by changing the length of the alkyl chain. Due to their comparable solubility parameters and similar chemical structures to phthalate plasticizers, the prepared isosorbide esters exhibit good compatibility with PVC. Oleic acid is a long-chain alkane with unsaturated double bonds. Some studies have reported that by esterifying oleic acid with isosorbide and then carrying out an epoxidation reaction, epoxy polar groups are introduced. Using the gel theory, this can be explained by the fact that the epoxy groups in the plasticizer form hydrogen bonds with the PVC molecular chains, thereby breaking the entanglement between the macromolecular chains and achieving a plasticizing effect.
[0004] In addition to good plasticizing effects, plasticizers should also possess good anti-migration and thermal stability. Patent CN114014870A discloses a method for preparing isosorbide ester bio-based plasticizers, along with its products and applications. The method includes: using isosorbide and a monocarboxylic acid as raw materials, undergoing an esterification reaction under the action of a catalyst to obtain isosorbide esters; then, using the isosorbide esters as raw materials, undergoing an oxidation reaction to obtain epoxy isosorbide esters. The isosorbide esters and epoxy isosorbide ester bio-based plasticizers prepared by this patent can be applied to the preparation of PVC composite materials, replacing some traditional phthalate plasticizers. The prepared PVC composite materials exhibit excellent mechanical and processing properties.
[0005] Patent CN114591537A discloses a bio-based solvent-resistant plasticizer and its preparation method. The plasticizer is composed of modified dioleoyl isosorbide dioleate, tris(ethyl butyrate) isocyanurate, and tetrabutylammonium chloride. The preparation method of the modified dioleoyl isosorbide dioleate involves first modifying the epoxy groups of the epoxy dioleoyl isosorbide dioleate by branching with phosphate esters, and then capping the resulting hydroxyl groups with acetic anhydride to finally obtain the modified dioleoyl isosorbide dioleate. However, this patent has a lengthy experimental process and requires the use of multiple plasticizers to achieve the desired effect of improving the flexibility, tensile strength, and extraction resistance of polyethylene resin. For example, after mixing 70g of PE with 30g of plasticizer, the elongation at break is 100%-150%, and the mass loss in cyclohexane and petroleum ether is between 19.8%-23.6%, which is too high.
[0006] Patent CN116425766A discloses an epoxy isosorbide ester plasticizer and its preparation method. The plasticizer is specifically epoxy isosorbide linoleic acid ester (EGLA-ISB), prepared by esterification and epoxidation of isosorbide and linoleic acid. This EGLA-ISB plasticizer successfully avoids the constraints between molecular weight and compatibility. The overall properties (mechanical properties, thermal stability, and migration resistance) of PVC plasticized with EGLA-ISB are superior to those of DOTP-plasticized PVC. Compared to oleic acid (AR-500ml / 58RMB), linolenic acid (GC-500ml / 2768RMB) is more expensive (data from Maclean's reagents). When 50 parts of EGLA-ISB are added to 100 parts of polyvinyl chloride to form a test piece, its elongation at break is 387%. Summary of the Invention
[0007] In view of the problems and shortcomings of the existing technology, the purpose of this invention is to provide an acetylsorbitol ester bio-based plasticizer, its preparation method and application.
[0008] To achieve the objectives of this invention, the technical solution adopted is as follows:
[0009] The first aspect of this invention provides a method for preparing an acetylosyl ester bio-based plasticizer, the method comprising: mixing epoxy isosorbide oleate with acetic anhydride and a strong acid cation exchange resin to obtain a mixture; heating the mixture to 100℃-130℃ and maintaining the temperature for reaction; and obtaining the acetylosyl ester bio-based plasticizer after the reaction is completed.
[0010] Furthermore, the mass ratio of the epoxy isosorbide oleate, acetic anhydride, and strong acid cation exchange resin is 1:0.5-1:0.01-0.2.
[0011] Furthermore, the heat preservation reaction time is 6-10 hours.
[0012] Furthermore, the preparation method of the epoxidized isosorbide oleate is as follows: isosorbide and oleic acid are used as raw materials, and an esterification reaction is carried out under the action of a catalyst to obtain isosorbide oleate; the isosorbide oleate is then subjected to an epoxidation reaction to obtain epoxidized isosorbide oleate.
[0013] Furthermore, the molar ratio of isosorbide to oleic acid is 1:1-3, and the amount of catalyst used is 0.01-0.5% of the total mass of isosorbide and oleic acid.
[0014] Furthermore, the catalyst is any one of methanesulfonic acid, p-toluenesulfonic acid, and tetrabutyl titanate.
[0015] Furthermore, the specific process of the epoxidation reaction is as follows: the isosorbide oleate, the epoxidation catalyst, formic acid and hydrogen peroxide solution are mixed evenly, heated to 50-80℃, and reacted for 5-10 hours. After the reaction is completed, epoxy isosorbide oleate is obtained.
[0016] Furthermore, the ratio of isosorbide oleate, epoxidation catalyst, formic acid and hydrogen peroxide is 1:0.01-0.2:0.1-0.5:0.5-1.
[0017] Furthermore, the epoxidation catalyst is concentrated sulfuric acid or a strong acidic cation exchange resin.
[0018] A second aspect of the present invention provides an acetylsorbitol ester bio-based plasticizer prepared by the above preparation method.
[0019] A third aspect of the present invention provides the application of the above-mentioned acetylsorbitol ester bio-based plasticizer in PVC composite materials.
[0020] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0021] 1. This invention provides a method for preparing an acetylated isosorbide ester bio-based plasticizer. Using isosorbide and oleic acid as raw materials, four acetyl side groups are introduced onto the isosorbide oleate ester branch chain through esterification, epoxidation, and acetylation reactions to form an acetylated isosorbide ester bio-based plasticizer. The raw materials used in this method are all bio-based, environmentally friendly, non-toxic, and renewable, meeting the requirements of green chemistry.
[0022] 2. The acetylsorbitol ester bio-based plasticizer prepared in this invention exhibits excellent plasticizing effects on PVC. This is due, on the one hand, to the presence of more oxygen atoms and polar groups, which enable stronger interactions with the PVC macromolecular chains, thus achieving a plasticizing effect. On the other hand, the presence of two long alkyl chains with polar side groups in the plasticizer results in a larger free volume, further enhancing its plasticizing properties.
[0023] 3. Compared with traditional phthalate plasticizers (dioctyl phthalate plasticizer and tributyl acetyl citrate), the PVC test pieces plasticized by the acetyl isosorbide ester bio-based plasticizer prepared in this invention have higher elongation at break, better thermal stability and lower migration.
[0024] 4. Compared with the use of multiple plasticizers in combination in the prior art (patent CN114591537A), the use of the acetyl isosorbide ester bio-based plasticizer prepared in this invention to plasticize PVC has lower migration and lower mass loss rate. Attached Figure Description
[0025] Figure 1 The infrared spectrum of the acetylsorbitol oleate prepared in this invention;
[0026] Figure 2 The 1H NMR spectrum of the acetylsorbitol oleate prepared in this invention;
[0027] Figure 3 The image shows the transmittance results of the PVC composite material specimens prepared according to the present invention. Detailed Implementation
[0028] The following embodiments are only for further elaboration of the present invention. It should be noted that all techniques and scientific terms used in this invention, unless otherwise stated, have the same meaning as those in the technical field to which this invention pertains. Experimental methods in the following embodiments that do not specify specific conditions all employ conventional techniques in this technical field or follow the conditions recommended by the manufacturer; reagents or instruments whose manufacturers are not specified are all commercially available conventional products.
[0029] To enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments.
[0030] The sources of the raw materials used in the embodiments and comparative examples of this invention are as follows:
[0031] Polyvinyl chloride (PVC), industrial grade, was purchased from Shanghai Chlor-Alkali Chemical Co., Ltd. Isosorbide (IS, 97%) was purchased from Aladdin Biochemical Technology Co., Ltd. Oleic acid (AR) and dioctyl phthalate (DOP, AR) were purchased from Sinopharm Chemical Reagent Co., Ltd. Methanesulfonic acid (99%), p-toluenesulfonic acid (99%), tetrabutyl titanate (AR), tributyl acetyl citrate (97%), and formic acid (85%) were purchased from Shanghai Maclean Biochemical Technology Co., Ltd. Toluene, concentrated sulfuric acid, and 30% hydrogen peroxide were purchased from Luoyang Chemical Reagent Factory. Strong acid cation exchange resin (AR) was purchased from Tianjin Kemeio Chemical Reagent Co., Ltd.
[0032] (I) Preparation of acetylated isosorbide ester bio-based plasticizer
[0033] Example 1
[0034] An acetylated isosorbide ester bio-based plasticizer, prepared by the following steps:
[0035] (1) Isosorbide (IS) and oleic acid (OA) in a molar ratio of 1:2 were added to 10 mL of toluene and mixed thoroughly. The reaction system was heated to 120 °C under a nitrogen atmosphere. Then, 0.1 wt% of p-toluenesulfonic acid (the total mass of isosorbide and oleic acid) was added to the reaction solution, and the reaction system was heated to 180 °C for 8 h. After the reaction was completed, the reaction solution was neutralized with NaOH solution, the upper liquid was extracted, and purified by rotary evaporation at 120 °C to obtain the brown product isosorbide oleate (IOA) with a yield of 79.4%.
[0036] (2) Isosorbide oleate, concentrated sulfuric acid, formic acid, and 30% hydrogen peroxide solution in a mass ratio of 1:0.01:0.3:0.5 were added to a three-necked flask. The flask was heated to 50°C while stirring, and the reaction was carried out for 5 hours. After the reaction was completed, the supernatant was obtained by centrifugation. The supernatant was washed with deionized water until neutral, and then rotary evaporated at 100°C to obtain the yellow product epoxy isosorbide oleate (EIOA).
[0037] (3) Epoxy isosorbide oleate, acetic anhydride, and strongly acidic cation exchange resin in a mass ratio of 1:0.5:0.1 were added to a three-necked flask, and the mixture was stirred and heated to 100°C for 6 hours. After the reaction was completed, the reaction solution was purified to obtain a pale yellow product, acetylated isosorbide oleate (AIOA), which is an acetylated isosorbide ester bio-based plasticizer.
[0038] Example 2
[0039] An acetylated isosorbide ester bio-based plasticizer, prepared by the following steps:
[0040] (1) Isosorbide (IS) and oleic acid (OA) in a molar ratio of 1:3 were added to 10 mL of toluene and mixed thoroughly. The reaction system was heated to 120 °C under a nitrogen atmosphere. Then, tetrabutyl titanate (0.5 wt% of the total mass of isosorbide and oleic acid) was added to the reaction solution, and the reaction system was heated to 230 °C and reacted for 12 h. After the reaction was completed, the reaction solution was neutralized with NaOH solution, the upper liquid was extracted, and purified by rotary evaporation at 120 °C to obtain the brown product isosorbide oleate (IOA) with a yield of 70.4%.
[0041] (2) Isosorbide oleate, a strong acidic cation exchange resin, formic acid, and 30% hydrogen peroxide solution in a mass ratio of 1:0.2:0.5:1 were added to a three-necked flask. The flask was heated to 80°C while stirring, and the reaction was carried out for 10 hours. After the reaction was completed, the supernatant was obtained by centrifugation. The supernatant was washed with deionized water until neutral, and then rotary evaporated at 100°C to obtain the yellow product epoxy isosorbide oleate (EIOA).
[0042] (3) Epoxy isosorbide ester, acetic anhydride, and strongly acidic cation exchange resin in a mass ratio of 1:1:0.2 were added to a three-necked flask, and the mixture was heated to 130°C while stirring, and reacted for 8 hours. After the reaction was completed, the reaction solution was purified to obtain a pale yellow product, acetylated isosorbide oleate (AIOA), which is an acetylated isosorbide ester bio-based plasticizer.
[0043] Example 3
[0044] An acetylated isosorbide ester bio-based plasticizer, prepared by the following steps:
[0045] (1) Isosorbide (IS) and oleic acid (OA) in a molar ratio of 1:2.1 were added to 10 mL of toluene and mixed thoroughly. The reaction system was heated to 120 °C under a nitrogen atmosphere. Then, 0.3 wt% methanesulfonic acid (based on the total mass of isosorbide and oleic acid) was added to the reaction solution, and the reaction system was heated to 190 °C for 8 h. After the reaction was completed, the reaction solution was neutralized with NaOH solution, the upper liquid was extracted, and purified by rotary evaporation at 120 °C to obtain the brown product isosorbide oleate (IOA) with a yield of 80.2%.
[0046] (2) Isosorbide ester, a strong acidic cation exchange resin, formic acid, and 30% hydrogen peroxide solution in a mass ratio of 1:0.1:0.3:0.65 were added to a three-necked flask, stirred, and heated to 60°C for 6 hours. After the reaction was completed, the supernatant was obtained by centrifugation. The supernatant was washed with deionized water until neutral and then rotary evaporated at 100°C to obtain the yellow product epoxy isosorbide oleate (EIOA).
[0047] (3) Epoxy isosorbide ester, acetic anhydride, and strongly acidic cation exchange resin in a mass ratio of 1:0.6:0.1 were added to a three-necked flask, and the mixture was stirred while being heated to 120°C for 7 hours. After the reaction was completed, the reaction solution was purified to obtain a pale yellow product, acetylated isosorbide oleate (AIOA), which is an acetylated isosorbide ester bio-based plasticizer.
[0048] Example 4
[0049] An acetylated isosorbide ester bio-based plasticizer, prepared by the following steps:
[0050] (1) Isosorbide (IS) and oleic acid (OA) in a molar ratio of 1:2.2 were added to 10 mL of toluene and mixed thoroughly. The reaction system was heated to 130 °C under a nitrogen atmosphere. Then, 0.4 wt% of p-toluenesulfonic acid (the total mass of isosorbide and oleic acid) was added to the reaction solution, and the reaction system was heated to 200 °C for 10 h. After the reaction was completed, the reaction solution was neutralized with NaOH solution, the upper liquid was extracted, and purified by rotary evaporation at 120 °C to obtain the brown product isosorbide oleate (IOA) with a yield of 81.7%.
[0051] (2) Isosorbide ester, concentrated sulfuric acid, formic acid, and 30% hydrogen peroxide solution in a mass ratio of 1:0.05:0.2:0.7 were added to a three-necked flask, stirred, and heated to 70°C for 8 hours. After the reaction was completed, the supernatant was obtained by centrifugation. The supernatant was washed with deionized water until neutral and then rotary evaporated at 100°C to obtain the yellow product epoxy isosorbide oleate (EIOA).
[0052] (3) Epoxy isosorbide ester, acetic anhydride, and strongly acidic cation exchange resin in a mass ratio of 1:0.7:0.15 were added to a three-necked flask, and the mixture was stirred while being heated to 130°C for 6 hours. After the reaction was completed, the reaction solution was purified to obtain a pale yellow product, acetylated isosorbide oleate (AIOA), which is an acetylated isosorbide ester bio-based plasticizer.
[0053] (II) Preparation of PVC composite materials
[0054] Example 5
[0055] A PVC composite material specimen was prepared by a solvent method. The specific preparation steps are as follows:
[0056] By weight, 100 parts of PVC and tetrahydrofuran were placed in a beaker, sealed with sealing film, and stirred on a strong magnetic stirrer to obtain a transparent solution. Then, 40 parts of the AIOA prepared in Example 1 were added to the beaker, and stirring was continued until homogeneous to obtain a mixture. The mixture was poured into a petri dish, and after the solvent had fully evaporated, an AIOA-40 sample was obtained.
[0057] Example 6
[0058] A PVC composite material specimen was prepared by a solvent method. The specific preparation steps are as follows:
[0059] By weight, 100 parts of PVC and tetrahydrofuran were placed in a beaker, sealed with sealing film, and stirred on a strong magnetic stirrer to obtain a transparent solution. Then, 50 parts of the AIOA prepared in Example 1 were added to the beaker, and stirring was continued until homogeneous to obtain a mixture. The mixture was poured into a petri dish, and after the solvent had fully evaporated, an AIOA-50 sample was obtained.
[0060] Example 7
[0061] A PVC composite material specimen was prepared by a solvent method. The specific preparation steps are as follows:
[0062] By weight, 100 parts of PVC and tetrahydrofuran were placed in a beaker, sealed with sealing film, and stirred on a strong magnetic stirrer to obtain a transparent solution. Then, 60 parts of the AIOA prepared in Example 1 were added to the beaker, and stirring was continued until homogeneous to obtain a mixture. The mixture was poured into a petri dish, and after the solvent had fully evaporated, an AIOA-60 sample was obtained.
[0063] Comparative Example 1
[0064] By weight, 100 parts of PVC and tetrahydrofuran were placed in a beaker, sealed with sealing film, and stirred on a strong magnetic stirrer to obtain a transparent solution. Then, 50 parts of dioctyl phthalate (DOP) were added to the beaker, and stirring was continued until a mixture was obtained. The mixture was poured into a petri dish, and after the solvent had fully evaporated, DOP-50 test pieces were obtained.
[0065] Comparative Example 2
[0066] By weight, 100 parts of PVC and tetrahydrofuran were placed in a beaker, sealed with sealing film, and stirred on a strong magnetic stirrer to obtain a transparent solution. Then, 50 parts of acetylthiol tributyl citrate (ATBC) were added to the beaker, and the mixture was stirred until homogeneous to obtain a mixed solution. The mixed solution was poured into a petri dish, and after the solvent had fully evaporated, ATBC-50 test pieces were obtained.
[0067] (III) Structural Characterization and Performance Testing
[0068] 1. Structural characterization of acetylated isosorbide ester bio-based plasticizer
[0069] Infrared spectroscopy
[0070] The Fourier transform infrared (FTIR) spectra of the EIOA and AIOA samples prepared in Example 1 were measured using a Tensor II (BRUKER, USA) infrared spectrometer. The measurements were performed in total reflectance mode with a resolution of 4 cm⁻¹. -1 The wavenumber range is 4000-400cm. -1 The result is as follows Figure 1 As shown.
[0071] from Figure 1 As can be seen, compared with the EIOA curve, the AIOA curve has a 836cm... -1 The stretching vibration peak of the epoxy bond (COC) disappeared, and the epoxy value decreased to 0.23%, indicating that the epoxy bond in the EIOA structure was successfully depolymerized and esterified. This invention successfully prepared AIOA.
[0072] 1H NMR spectrum
[0073] The EIOA and AIOA samples prepared in Example 1 were subjected to 1H NMR spectroscopy. The solvent used was deuterated chloroform (CDCl3), and the internal standard was tetramethylsilane (TMS). The results are as follows: Figure 2 As shown.
[0074] contrast Figure 2 EIOA and AIOA 1 In the H NMR curves, the peak at 1.4 ppm in the EIOA curve is attributed to the proton signal on carbon atom e, and the peak at 2.8 ppm is attributed to the proton signal on carbon atom d in the epoxide bond. The AIOA curves show that after the ring-opening experiment, the proton signal peaks on d and e in the EIOA curve disappear, while proton peaks on g and f appear. Specifically, the peak at 4.9 ppm corresponds to the proton signal at f after the epoxide bond opens, and the peak at 2.0 ppm corresponds to the proton peak of the methyl group at g after acetylation. This indicates that the epoxide bond in the EIOA curve is converted into a functional group in the AIOA curve, demonstrating the successful progress of the ring-opening acetylation reaction.
[0075] 2. Performance testing of PVC composite material specimens
[0076] Transmittance test
[0077] The ultraviolet absorption and transmission spectra of the PVC samples prepared in Examples 5-7 and Comparative Examples 1-2 were measured using a UV-9000S ultraviolet spectrophotometer (Shanghai Yuanxi Instrument Co., Ltd., China). Each sample was cut into a 2cm × 4cm rectangle and placed on a thin film sample holder. The wavelength range was 200-900nm, with air as the blank reference. The test results are shown in [reference needed]. Figure 3 .
[0078] from Figure 3 It can be observed that in the visible light range of 400-800 nm, the transmittance of PVC samples plasticized with AIOA can reach over 80%, and the AIOA content has little effect on the transmittance of the samples; a lower amount of plasticizer can achieve higher transmittance. Furthermore, the transmittance of PVC samples plasticized with AIOA is higher than that of DOP-50 and ATBC-50. Therefore, the acetylated isosorbide ester bio-based plasticizer prepared in this invention can be used as a plasticizer for transparent materials.
[0079] Thermal stability test
[0080] The thermal stability of PVC specimens prepared in Examples 5-7 and Comparative Examples 1-2 was tested using a STA449F3 (NETZSCH, Germany) simultaneous thermal analyzer. The test was conducted under a nitrogen atmosphere with sample masses of 3-5 mg, a temperature range of 30-600 °C, and a heating rate of 20 °C / min. The TGA data for different PVC specimens are shown in Table 1, where T... 5% T10% T 50% These represent the temperatures at which the mass loss rate is 5%, 10%, and 50%, respectively.
[0081] Table 1. Thermogravimetric data of PVC test pieces
[0082] Sample Name AIOA-40 AIOA-50 AIOA-60 DOP-50 ATBC-50 T5%·(℃) 270.7 280.9 282.2 285.1 257.0 T10%·(℃) 290.8 298.0 298.7 296.6 272.5 T50%·(℃) 359.7 366.5 367.1 327.6 315.9
[0083] As shown in Table 1, ATBC-50 exhibits the worst thermal stability among the three plasticizers. Below 300℃, the thermal stability of DOP-50 and the AIOA series samples is not significantly different, but above 300℃, the thermal stability of the AIOA series samples is significantly higher than that of DOP-50. Overall, the AIOA-plasticized samples prepared in this invention demonstrate better thermal stability.
[0084] Dynamic thermomechanical behavior testing
[0085] The dynamic thermomechanical behavior of PVC specimens prepared in Examples 5-7 and Comparative Examples 1-2 was characterized using a Q800 Dynamic Thermomechanical Analyzer (DMA) from TA Instruments, Inc. Thin film tensile and multi-frequency strain modes were selected for testing, with a frequency of 1 Hz and a heating rate of 3 °C / min from -30 °C to 100 °C. The test results are shown in Table 2.
[0086] Table 2. Dynamic Thermomechanical Data
[0087] Sample Name AIOA-40 AIOA-50 AIOA-60 DOP-50 ATBC-50 Tg (°C) 49.3 43.5 35.1 18.3 14.9
[0088] Table 2 shows that the T values of PVC samples using different plasticizers... g All were below 50℃, while pure PVC T g Generally around 88℃, therefore, all plasticizers prepared in this invention have a plasticizing effect on PVC.
[0089] Mechanical performance testing
[0090] The tensile properties of PVC specimens prepared in Examples 5-7 and Comparative Examples 1-2 were tested using a UTM-2502 microcomputer-controlled electronic universal testing machine (Shenzhen Xin Sansi Metrology Technology Co., Ltd., China). The PVC specimens were cut into dumbbell-shaped strips (gauge length 13 mm, width 2 mm) using a standard cutter. The tensile properties of each sample were tested at room temperature (25±5℃) with a tensile rate controlled at 50 mm / min. Each sample was tested five times under the same conditions, and the average value was taken as the final result of its tensile properties. The mechanical property results of different samples are shown in Table 3.
[0091] Table 3. Mechanical properties of PVC test pieces
[0092] Example Sample Name Tensile strength (MPa) Elongation at break (%) Young's modulus (MPa) Example 5 AIOA-40 24.9·±·0.9 601.2·±·14.6 6.7·±·0.3 Example 6 AIOA-50 22.9·±·0.4 638.3·±·11.5 5.6·±·0.1 Example 7 AIOA-60 21.8·±·0.4 680.2·±·7.9 4.8·±·0.1 Comparative Example 1 DOP-50 24.5·±·0.2 650.1·±·6.2 5.8·±·0.3 Comparative Example 2 ATBC-50 28.0·±·0.6 603.4·±·11.4 8.4·±·0.3
[0093] Table 3 shows that all plasticizers exhibit good plasticizing effects. The stress-strain curves of AIOA-40 and ATBC-50 are similar, indicating comparable plasticizing effects in mechanical properties. The stress-strain curves of AIOA-50 and DOP-50 are also similar. This suggests that, with the same plasticizer content, AIOA's plasticizing effect is comparable to or superior to DOP and ATBC in terms of mechanical properties. With increasing plasticizer content, the tensile strength of the specimens gradually decreases, while the elongation at break gradually increases, with AIOA-60 reaching a maximum elongation at break of 680.2%. Therefore, compared with traditional phthalate plasticizers, the acetylated isosorbide ester plasticizer prepared in this invention has better mechanical properties.
[0094] Anti-volatile test
[0095] Referring to ISO 176-2005, "Activated Carbon Adsorption Method", the PVC test pieces prepared in Examples 5-7 and Comparative Examples 1-2 were subjected to anti-volatility tests for 24 hours. The test results are shown in Table 4. The volatilization rate was calculated using the following formula, where w0 is the initial mass of the test piece and w1 is the final mass of the test piece.
[0096]
[0097] Table 4. Volatility data of PVC test pieces
[0098] Example Example 5 Example 6 Example 7 Comparative Example 1 Comparative Example 2 Sample Name AIOA-40 AIOA-50 AIOA-60 DOP-50 ATBC-50 Quality loss rate (%) 3.5 3.2 2.9 2.5 7.8
[0099] Table 4 shows that ATBC-50 had the highest mass loss rate (7.8%), while DOP-50 and AIOA-50 had comparable mass loss rates (both below 5%). Furthermore, with increasing plasticizer content (Examples 5-7), the mass loss rate of the PVC samples in the anti-volatility test gradually increased. This is because AIOA contains more polar groups than DOP and ATBC. More polar groups facilitate a stronger interaction between the plasticizer and the PVC chain. As the plasticizer content increases, there are relatively more polar groups, thus increasing the anti-volatility. Therefore, the acetylated isosorbide ester bio-based plasticizer prepared in this invention exhibits good anti-volatility properties.
[0100] Extraction resistance test
[0101] The PVC specimens prepared in Examples 5-7 and Comparative Examples 1-2 were subjected to extraction resistance tests according to the standard ISO 175-2011 Plastics—Determination of the immersion effect of liquid chemicals. Petroleum ether, anhydrous ethanol, and deionized water were selected to simulate non-polar, polar, and aqueous environments, respectively. The test time was 24 hours. The specific test results are shown in Table 5. The mass loss rate in the table was calculated in the same way as above.
[0102] Table 5. Extraction resistance of PVC test pieces
[0103]
[0104] As shown in Table 5, in an aqueous environment, the mass loss rate of all PVC samples was less than 5%, with DOP-50 performing the best. This is because it has a hydrophobic benzene ring structure. AIOA and ATBC contain more polar groups such as acetyl and ester groups, so their performance in an aqueous environment is not as good as DOP-50, but it is still less than 5% over a longer period of time.
[0105] In a polar environment, with the same plasticizer content, AIOA-50 exhibited the lowest mass loss rate, indicating that AIOA possesses superior anti-extraction capabilities compared to DOP and ATBC. Furthermore, the mass loss rate of the samples gradually increased with increasing AIOA content, likely due to the increased content of polar groups, which facilitate migration; however, the mass loss rate of all AIOA samples remained below 5%.
[0106] In a non-polar environment, the mass loss rate of all AIOA specimens was less than 5%, while the mass loss rate of DOP-50 was as high as 18.2% and that of ATBC-50 was 9.1%. This indicates that the AIOA prepared in this invention has better resistance to extraction in a non-polar environment.
[0107] In summary, in aqueous environments, the AIOA prepared by this invention exhibits comparable pull-out resistance to the other two plasticizers, making it suitable for use in packaging materials. However, in both polar and non-polar solvent environments, the AIOA prepared by this invention demonstrates better pull-out resistance compared to ATBC and DOP. This is likely due to AIOA's larger relative molecular weight, longer molecular chain, and more polar groups, resulting in better compatibility with PVC and a lower likelihood of migration from PVC.
[0108] Migration resistance test
[0109] Migration resistance was determined for PVC test pieces prepared according to the standard Examples 5-7 and Comparative Examples 1-2 of 82 / 711 / EEC. The test time was 24 hours, and the test solvent was n-hexane. The test results are shown in Table 6. The mass loss rate in the table is calculated in the same way as above.
[0110] Table 6. Migration resistance data of PVC test pieces
[0111] Example Example 5 Example 6 Example 7 Comparative Example 1 Comparative Example 2 Sample Name AIOA-40 AIOA-50 AIOA-60 DOP-50 ATBC-50 Quality loss rate (%) 2.4 2.8 3.8 18.3 11.1
[0112] The results in Table 6 show that DOP-50 exhibits the worst migration resistance in a hexane environment, with a mass loss rate of 18.3%, followed by ATBC-50 (11.0%), while AIOA-50 has a mass loss rate of only 2.8%. This indicates that AIOA prepared in this invention has better migration resistance compared to DOP and ATBC.
[0113] In summary, this invention provides a method for preparing an acetylsorbitol ester bio-based plasticizer. This plasticizer is prepared by sequentially undergoing esterification, epoxidation, and acetylation reactions with isosorbide and oleic acid as raw materials. Compared to traditional phthalate plasticizers (ATBC and DOP) and existing isosorbide ester plasticizers, the acetylsorbitol ester bio-based plasticizer prepared in this invention produces polyvinyl chloride (PVC) sheets with higher elongation at break (601.2%-680.2%) and better thermal stability (T). 10% At a temperature of 298.0℃, the mass loss rate was less than 5% in various migration experiments. Furthermore, this invention provides a new approach for preparing isosorbide-based plasticizers with high plasticizing effect, single plasticizer use, bio-based origin, low migration rate, and low cost.
[0114] The above embodiments are specific implementations of the present invention, but the implementation of the present invention is not limited to the above embodiments. Any other combination, change, modification, substitution, or simplification that does not exceed the design concept of the present invention shall fall within the protection scope of the present invention.
Claims
1. A method for preparing an acetylsorbitol ester bio-based plasticizer, characterized in that, The preparation method includes: Epoxy isosorbide oleate was mixed with acetic anhydride and a strong acid cation exchange resin to obtain a mixture; the mixture was heated to 100-130℃ and kept at that temperature for 6-10 hours. After the reaction was completed, acetyl isosorbide ester bio-based plasticizer was obtained. The preparation method of the epoxy isosorbide oleate is as follows: (1) Using isosorbide and oleic acid as raw materials, an esterification reaction is carried out under the action of a catalyst to obtain isosorbide oleate; the catalyst is any one of methanesulfonic acid, p-toluenesulfonic acid and tetrabutyl titanate; (2) Mix the isosorbide oleate, epoxidation catalyst, formic acid and hydrogen peroxide solution evenly, heat to 50-80℃, react for 5-10h, and obtain epoxy isosorbide oleate after the reaction is completed.
2. The method for preparing the acetylsorbitol ester bio-based plasticizer according to claim 1, characterized in that, The mass ratio of epoxy isosorbide oleate, acetic anhydride and strong acid cation exchange resin is 1:0.5-1:0.01-0.
2.
3. The method for preparing the acetylsorbitol ester bio-based plasticizer according to claim 1, characterized in that, The molar ratio of isosorbide to oleic acid is 1:1-3, and the amount of catalyst used is 0.01-0.5% of the total mass of isosorbide and oleic acid.
4. The method for preparing the acetylsorbitol ester bio-based plasticizer according to claim 1, characterized in that, The mass ratio of isosorbide oleate, epoxidation catalyst, formic acid and hydrogen peroxide is 1:0.01-0.2:0.1-0.5:0.5-1.
5. The method for preparing the acetylsorbitol ester bio-based plasticizer according to claim 1, characterized in that, The epoxidation catalyst is concentrated sulfuric acid or a strong acid cation exchange resin.
6. An acetylsorbitol ester bio-based plasticizer prepared by the preparation method of claim 1.
7. The application of the acetylsorbitol ester bio-based plasticizer as described in claim 6 in the preparation of PVC composite materials.
Citation Information
Patent Citations
Preparation method of isosorbide ester bio-based plasticizer and product and application of isosorbide ester bio-based plasticizer
CN114014870A
Preparation method and application of vegetable oil-based environment-friendly plasticizer with high thermal stability
CN111777510A
Epoxy isosorbide ester plasticizer and preparation method thereof
CN116425766A
